Legal Consequences of Difference in The Results of Two Visum Et Repertum in Proving Criminal Case in Indonesia - Firmansyah, Muhammad; Simangunsong, Frans (Magister Ilmu Hukum Fakultas Hukum Universitas 17 Agustus 1945 Surabaya, 2024)
In criminal cases, visual evidence is used to reveal the cause and effect of a criminal act. If there are two different visual outcomes in Brigadier Joshua's case, then the question arises as to which choice of visum will be recognized as valid evidence by the judge in considering his decision. The formulation of the problem in this study is how the legal consequences of the difference in the results of two visum et repertum in the evidence system in Indonesia. This study aims to examine the legal consequences of the difference in the results of the two visum et repertum in proving criminal cases in Indonesia. This study used normative legal research. The approach used in this study is to use a statutory approach and a conceptual approach. The results of this study showed that the case of the visual results in Brigadier Josua had 2 different results. Therefore, the principle of Indonesian criminal procedural law, finding material truth is very important in proof in the criminal justice process. What is meant by